THE CONCEPT OF SMALL BUSINESS AND ENTREPRENEURSHIP AND THEIR DEVELOPMENT FEATURES (Universal International Scientific Journal, 2026)
This article examines the essence and main features of small business and entrepreneurship, their role in the modern economy, as well as the features of their development in the conditions of market transformation. The study pays special attention to the experience of the Republic of Uzbekistan, analysis of statistical data and measures of state support for small business. Based on the analysis, the main problems were identified and recommendations were developed for the further development of small business.
Keywords: small business; entrepreneurship; economy